The Imbalance of MMP-2/TIMP-2 and MMP-9/TIMP-1 Contributes to Collagen Deposition Disorder in Diabetic Non-Injured Skin - Zhou, Peng; Yang, Chao; Zhang, Shan; Ke, Zun-Xiang; Chen, Dian-Xi; Li, Yi-Qing; Li, Qin (Frontiers in Endocrinology, 2021)
Early diagnosis and treatment of diabetes and its cutaneous complications become increasingly recognized. In Masson’s trichrome staining, dermal collagen of diabetic non-injured skin was disordered and the density was variable, which were dispersed or arranged in vague fascicles. The collagen type I sequencing results of RNA sequencing-based transcriptome analysis of three primary human skin-cell types under high glucose were analyzed, i.e., dermal fibroblasts, dermal microvascular endothelial cells, and epidermal keratinocytes. It showed that both COL1A1 and COL1A2 mRNAs expressions were reduced in human dermal fibroblasts. The ratio of MMP-2/TIMP-2 and MMP-9/TIMP-1 in high glucose -treated human dermal fibroblasts were observed to be increased. Through inhibiting MMP-2 and MMP-9 with SB-3CT, collagen deposition disorder of skin in STZ induced diabetes mice was alleviated. The imbalance of MMP2/TIMP2 and MMP9/TIMP1 contribute to the non-injured skin disorder of collagen deposition in diabetes, providing an idea for against diabetes skin complications in clinic early.